Knowledge, attitudes and practices on healthy eating in adolescents of two Public Educational Institutions, Lima East-2018 - Fustamante Ticlla, Yanina (2019)
Objective: Determine the level of knowledge, attitudes and practices on healthy eating in adolescents from two educational institutions. Methodology: Is non-experimental design, cross-sectional, and descriptive type. The population was made up of all the students of the 1st and 5th grade of the secondary level. The sample consisted of 589 students. The instrument was an applied questionnaire of 42 questions, knowledge, attitudes and practices. Results: It was found that 57% of adolescents have a regular level of knowledge, 83.4% have a favorable attitude and 78.2% of adolescents presented an inadequate practice in healthy eating. Conclusions: More than half of adolescents have a level of regular knowledge. On the other hand, it was found that they presented a favorable attitude in opting for a healthy diet. However, the largest proportion do not practice it adequately.